Kajian Peningkatan Pelayanan Terhadap Sistem Informasi dengan Augmanted Reality Wayfinding di Bandar Udara Internasional Ahmad Yani Semarang - Machmiyana, Ichyu; Rafelly, Kevin; Sonhaji, Imam; Pratiwi, Ayu Kumala; Kusumah, Muhammad Chandra (Politeknik Penerbangan Indonesia Curug, 2024)
Information services are one of the facilities that provide comfort to service users, one of the information service facilities is signage, flight information displey system, and curtomer service. Especially in the lobby area, the lack of directions or Guidance needed by service users so that service improvement is needed. The objectives of this research are (i). To find out the needs of improving the service of Jenderal Ahmad Yani Semarang International Airport on the information system (ii). to know the description of Augmanted Reality Wayfinding. Quantitative descriptive research method through Ministerial Decree number 22 of 2005 concerning the Enforcement of Indonesian National Standard (SNI) 03-7094-2005 Regarding Signs in Airport Terminals as Mandatory Standards. The research instrument used observation as evidenced by documentation and questionnaires. The results of the study, especially in the passenger terminal lobby, showed that 44% of passengers expressed dissatisfaction with the availability of information-giving facilities, because of this there is a need for tools to support AR Wayfinding which can make it easier for service users to find the location they want to go to.